2002
DOI: 10.1179/027249302125000841
|View full text |Cite
|
Sign up to set email alerts
|

The post-mortem pathology of HIV-1-infected African children

Abstract: A retrospective review of autopsy findings and medical records in 33 HIV-infected children living in a Kenyan orphanage is described. Their ages ranged from 1 month to 18 years and median age at death was 71 months (range 7-156). Respiratory disorders were probably the primary cause of death in 21 (64%), in 19 (90%) of whom pyogenic parenchymal lung disease was detected. A presumptive clinical diagnosis of pulmonary tuberculosis had been made in 14 (67%); these children also had a history of recurrent acute lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
1
11
1
Order By: Relevance
“… 1 , 4 – 7 The occurrence of bacterial infections in patients with HIV/AIDS is also a reflection of their immunosuppression, and the most frequent pathogens are Streptococcus pneumoniae, Staphylococcus aureus, Haemophilus influenzae, and Pseudomonas aeruginosa . 1 5 Rana et al analyzed autopsies in Kenya and showed an association between tuberculosis and BBP in 96% of patients with HIV/AIDS. 6 Even in pediatrics studies, BBP appeared as the major cause of ARF in autopsies of patients with HIV/AIDS.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 4 – 7 The occurrence of bacterial infections in patients with HIV/AIDS is also a reflection of their immunosuppression, and the most frequent pathogens are Streptococcus pneumoniae, Staphylococcus aureus, Haemophilus influenzae, and Pseudomonas aeruginosa . 1 5 Rana et al analyzed autopsies in Kenya and showed an association between tuberculosis and BBP in 96% of patients with HIV/AIDS. 6 Even in pediatrics studies, BBP appeared as the major cause of ARF in autopsies of patients with HIV/AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…Autopsy remains the gold standard for confirming the cause of death. Previous studies have shown that (partial) autopsy is a feasible procedure in Sub-Saharan Africa, both in study settings and as a general practice [5], [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary tuberculosis was found in 17.8% of the cases in the whole period of our study. Autopsy studies have found the presence of Mycobacterium tuberculosis infection in 5% -59% of cases [33][34][35][36][37][38]. Worldwide is known the importance of mycobacterial tuberculosis coinfection in HIV positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide is known the importance of mycobacterial tuberculosis coinfection in HIV positive patients. In developed countries, the prevalence of tuberculosis in autopsies of patients with HIV/AIDS is much lower than developing countries, like Brazil [33][34][35][36][37][38]. CMV pneumonitis was found in 21.1% of patients.…”
Section: Discussionmentioning
confidence: 99%